Pemacuan Pertumbuhan Melon (Cucumis melo L.) dengan Cendawan Mikoriza Arbuskula dan Bakteri Azospirillum sp. - Tetelepta, Lady Diana; ,, Triadiati; Sukarno, dan Nampiah (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTMelon (Cucumis melo L.) is a high economic value horticultural crop that is cultivated in some regions of Indonesia under fertilization management. Application of inorganic fertilizer continuously can reduce soil microbial abundance. One of the soil microbial that promote plant growth is arbuscular mycorrhizal fungi (AMF) and Azospirillum sp. The aim of this study was to analysed the effect of AMF and Azospirillum sp. in promoting growth and production of melon. The experiment was carried out in a greenhouse and was arranged in a completely randomized design with five replicates. Five treatments tested were: control, fertilized with NPK, inoculated with AMF, inoculated with Azospirillum sp., inoculated with AMF + Azospirillum sp. The results showed that the effect of AMF on root growth and shoot growth were similar to NPK fertilizer. Azospirillum sp. increased root growth. On the other side, the effect of Azospirillum sp. on shoot growth was similar to NPK fertilizer. However, AMF and Azospirillum sp. inoculation solely increased plant height, fruit weight, fruit diameter, flavor and length of fruit storage. Meanwhile, combination of AMF and Azospirillum sp. increased plant height, root growth, shoot growth, fruit weight, fruit diameter, flavor and length of fruit storage. This study revealed that application of AMF and Azospirillum sp. in melon cultivation was more effective and efficient than NPK fertilizer.Keywords: arbuscular mycorrhizal fungi, Azospirillum sp., Cucumis melo L.